ANALISIS SOLIDARITAS MEKANIK PADA ORGANISASI BAPAKAT ETNIS DAYAK KANAYATN DESA PANCAROBA KECAMATAN SUNGAI AMBAWANG - Alhafizah, Alhafizah; Bahari, Yohanes; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research was â€œThe Analysis of Mechanical Solidarity on Dayak Kanayatn Bapakat Organisation at Desa Pancaroba Kecamatan Sungai Ambawangâ€. The research problem was how did the mechanical solidarity on Dayak Kanayatn Bapakat Organisation at Desa Pancaroba Kecamatan Sungai Ambawang. The purpose of this research was described the mechanical solidarity based on strong collective awareness and repressive law systems in Bapakat organisation. The method conducted in this research was descriptive in qualitative form. The analysis of this research presented in qualitative descriptive with using four informants. The result finding showed that the mechanical solidarity on Dayak Kanayatn Bapakat organisation at Desa Pancaroba based on strong collective awareness and dominant of repressive law. Collective awareness form showed in work program of sport, such doing sport together like volleyball and football. In agriculture, there was an activity like farming paddy, potato and kind of herbs. In social and community, there was a social gathering every Sunday and in spirituality there was an activity of praying together on Bapakat organisation. The law on Bapakat organisation was repressive. The purpose of the law was to bring back the collective awareness of the members that break the rules on Bapakat organisation.Keywords: Collective Awareness, Dayak Kanayatn, Mechanical SolidarityÂ Â Â Â Â Â Â Â Â